Penyuluhan Tentang Pencegahan Preeklampsia Melalui Kontrol Tekanan Darah Pada Ibu Hamil Risiko Tinggi - Cici Pratiwi; Habil Harum; Halimatussakdiyah Lubis (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Preeclampsia is a pregnancy complication that can cause morbidity and mortality in both mothers and fetuses. This condition is characterized by increased blood pressure accompanied by proteinuria that appears after 20 weeks of pregnancy. One important step in preventing preeclampsia is to monitor blood pressure regularly, especially in pregnant women with high risk factors. This community service activity aims to increase pregnant women's knowledge about preventing preeclampsia through blood pressure control and a healthy lifestyle. The activity was carried out in the working area of Puskesmas X with 30 high-risk pregnant women participating. The methods used included lectures, interactive discussions, demonstrations of blood pressure measurement, and the distribution of educational leaflets. The results of the activity showed an increase in participants' knowledge from an average of 58% before the counseling to 90% after the counseling. Participants also showed an increase in motivation to monitor their blood pressure regularly and maintain a healthy diet. This activity is expected to support efforts to prevent pregnancy complications by increasing awareness and healthy behavior among pregnant women.